2014
DOI: 10.1038/psp.2014.21
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Modeling Reveals the Critical Knowledge Gaps in Bile Acid–Mediated DILI

Abstract: Bile salt export pump (BSEP) inhibition has been proposed to be an important mechanism for drug-induced liver injury (DILI). Modeling can prioritize knowledge gaps concerning bile acid (BA) homeostasis and thus help guide experimentation. A submodel of BA homeostasis in rats and humans was constructed within DILIsym, a mechanistic model of DILI. In vivo experiments in rats with glibenclamide were conducted, and data from these experiments were used to validate the model. The behavior of DILIsym was analyzed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 36 publications
(39 reference statements)
2
64
0
Order By: Relevance
“…A great amelioration is the incorporation of bile acid dynamics in the DILIsym [92], thus, the model includes not only the metabolic pathways, mitochondrial toxicity, key transporters, etc., but also the synthesis, uptake, recirculation, efflux, and hepatotoxicity of bile acids. This complex approach may help to reduce discrepancies originated from species differences as well as from in vitro and in vivo experimental data, thereby allowing improved prediction of BSEP-related DILI [92].…”
Section: In Silico Models For Predictions Of Cholestatic Effects Of Dmentioning
confidence: 99%
“…A great amelioration is the incorporation of bile acid dynamics in the DILIsym [92], thus, the model includes not only the metabolic pathways, mitochondrial toxicity, key transporters, etc., but also the synthesis, uptake, recirculation, efflux, and hepatotoxicity of bile acids. This complex approach may help to reduce discrepancies originated from species differences as well as from in vitro and in vivo experimental data, thereby allowing improved prediction of BSEP-related DILI [92].…”
Section: In Silico Models For Predictions Of Cholestatic Effects Of Dmentioning
confidence: 99%
“…Most importantly, the canalicular efflux transporter bile salt export pump (BSEP) seems to be the key player in the development of cholestatic DILI. This has been summarized by Vinken et al in an Adverse Outcome Pathway (AOP), and further confirmed by Woodhead et al by sensitivity analysis of a mechanistic model of cholestatic DILI (Vinken et al, 2013;Woodhead et al, 2014).…”
Section: Introductionmentioning
confidence: 84%
“…Kinetic parameters for the interaction of human transporters (NTCP, BSEP and OATPs) and bile acids are either not published with appropriate scaling factors or at best are available only for taurocholate, which is a minor BA in humans. In addition, Woodhead et al showed that BSEP abundance is the most important unknown kinetic parameter, that has a great influence on the outcome of the BA concentration in the liver in the presence of a BSEP inhibitor (Woodhead et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The full set of equations for DILIsym version 3A (and indeed for all versions of DILIsym past and present) is fully available to the members of the Initiative. Importantly, key equations from DILIsym have been published in the literature, including equations related to oxidative stress,5 bile acid homeostasis and transporter disruption,7, 9 mitochondrial dysfunction,10 and the dynamics of the innate immune system 11. These previous publications also provide significant insight into the scientific theory and knowledge behind the development of DILIsym.…”
Section: Methodsmentioning
confidence: 99%